(untitled) (Vietnam Journal of Community Medicine, 2022)
A prospective descriptive study was carried out at So Trang Obstetrics and Children’s Hospital from November 2020 to June 2021 on 250 patients after surgery. Objectives: (1) Determine the rate of infection after gynecological surgery at Soc Trang Obstetrics and Gynecology Hospital (2) Find out the results of patient care and some related factors. Objectives: (1) Determine the rate of infection after gynecological surgery at Soc Trang Obstetrics and Gynecology Hospital (2) Find out the results of patient care and some related factors. Results: Cardiovascular disease accounted for 4%, exhaustion accounted for 2.8%, diabetes accounted for 1.2%, and cardiovascular disease accounted for 0.8%. Hospital stay after appendectomy: > 7 days, accounting for 35.2%; Patients hospitalized for < 7 days accounted for 64.8%. The rate of hospital-acquired infections was 2.4% (Urinary tract infections: 0.4%, Surgical site infections: 1.6%; Skin and soft tissue infections: 0.4%. The results of care showed that the surgical wound dressings were changed from 24 to 48 hours after surgery, accounting for 2.4% in patients with hospital-acquired infections and 97.6% in patients without hospital-acquired infections. 6% of patients without UTI No Change of surgical wound dressing as indicated in patients with UTI accounted for 2.4% and patients without UTI accounted for 66%. Regarding the correct dressing change in patients with non-infected patients accounted for 97.6% and without proper dressing change in patients with hospital-acquired infections accounted for 2.4%. Regarding surgical drainage, correct QT interval in non-infected patients accounted for 97.2%, and no correct QT dressing in non-infected patients accounted for 0.4% and no correct QT dressing in patients with UTI accounted for 2.4% . There was a difference and statistically significant between patients who received care to change the surgical wound dressing from 24 - 48 h and did not change the dressing with nosocomial infection (p < 0.05), not found. the difference between changing the wound dressing as indicated; between changing surgical wound dressings according to technical procedures, between drain care and nosocomial infections (p > 0.05),